Digital energy visualizations in the workplace: the e-Genie tool. Issue 3 (3rd April 2018) - Spence, Alexa; Goulden, Murray; Leygue, Caroline; Banks, Nick; Bedwell, Ben; Jewell, Mike; Yang, Rayoung; Ferguson, Eamonn
ABSTRACT: Building management systems are designed for energy managers; there are few energy-feedback systems designed to engage staff. A tool, known as e-Genie, was created with the purpose of engaging workplace occupants with energy data and supporting them to take action to reduce energy use. Building on research insights within the field, e-Genie's novel approach encourages users to make plans to meet energy-saving goals, supports discussion and considers social energy behaviours ( e.g. discussing energy issues, taking part in campaigns) as well as individual actions. A field-based study of e-Genie indicated that visualizations of energy data were engaging and that the discussion 'Pinboard' was particularly popular. Pre- and post-survey ( N  = 77) evaluation of users indicated that people were significantly more concerned about energy issues and reported engaging more in social energy behaviour after about two weeks of e-Genie being installed. Concurrently, objective measures of electricity use decreased over the same period, and continued decreasing over subsequent weeks. Indications are that occupant-facing energy-feedback visualizations can be successful in reducing energy use in the workplace; furthermore, supporting social energy behaviour in the workplace is likely to be a useful direction for promoting action.